2019
DOI: 10.1371/journal.pone.0217056
|View full text |Cite
|
Sign up to set email alerts
|

Team sport expertise shows superior stimulus-driven visual attention and motor inhibition

Abstract: Previous studies on athletes’ cognitive functions have reported superior performance on tasks measuring attention and sensorimotor abilities. However, how types of sports training shapes cognitive profile remains to be further explored. In this study, we recruited elite athletes specialized in badminton (N = 35, female = 12) and volleyball (N = 29, female = 13), as well as healthy adult controls (N = 27, female = 17) who had not receive any regular sports training. All participants completed cognitive assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 51 publications
4
16
1
Order By: Relevance
“…Sport, given its dynamic nature, the ongoing interaction between different performers and the time constraints under which decisions must be made, represents an ideal vehicle to investigate the effects of long-term IC training in complex situations. Athletes practicing an open-skill sport (e.g., tennis, fencing, and soccer) requiring players to behave in a continuously changing environment 26 have recorded faster RT in Go/NoGo tasks 16 , 24 , 27 , as well as changes in brain structure and function within the IC network 16 , 19 , 26 , 28 31 compared to nonathletes. On the other hand, athletes practicing closed-skill sports (e.g., swimming, high jump, and ballet) requiring performance in a predictable and stable environment face only a few situations involving IC and exhibit lower performance on IC tasks compared to athletes practicing open-skill sports 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Sport, given its dynamic nature, the ongoing interaction between different performers and the time constraints under which decisions must be made, represents an ideal vehicle to investigate the effects of long-term IC training in complex situations. Athletes practicing an open-skill sport (e.g., tennis, fencing, and soccer) requiring players to behave in a continuously changing environment 26 have recorded faster RT in Go/NoGo tasks 16 , 24 , 27 , as well as changes in brain structure and function within the IC network 16 , 19 , 26 , 28 31 compared to nonathletes. On the other hand, athletes practicing closed-skill sports (e.g., swimming, high jump, and ballet) requiring performance in a predictable and stable environment face only a few situations involving IC and exhibit lower performance on IC tasks compared to athletes practicing open-skill sports 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Overney et al, (2008) found that not only did tennis players outperform non-athletes, but they outperformed triathletes too in measures of temporal processing. Similarly, Meng et al (2019) found that volleyball players performed better than badminton players on some tasks such as attentional alerting, whereas the badminton players performed better than volleyball players on measures such as processing speed. Future research might aim to investigate individual differences in visual attention function as measured by the MOA in further defined sporting categories in order to further our understanding of the attentional nature of the MOA.…”
Section: Sporting Expertise and Task Performancementioning
confidence: 84%
“…Reactive inhibitory control refers to the ability to withdraw from already-planned actions when necessary, and is thought to be a bottom-up, late correction process triggered by external signals ( e.g ., braking when a pedestrian suddenly crosses the street) ( Aron, 2011 ; Aron, Robbins & Poldrack, 2004 , 2014 ; Braver, 2012 ; Hampshire & Sharp, 2015 ). Previous studies found that athletes, especially those in open skill sports, exhibited a heightened capacity for inhibitory control ( Huijgen et al, 2015 ; Jacobson & Matthaeus, 2014 ; Meng et al, 2019 ; Yamashiro et al, 2015 ); however, most of the studies looked at reactive rather than proactive inhibitory control ( Heppe & Zentgraf, 2019 ; Liao, Meng & Chen, 2017 ; Wang et al, 2013 ). Using a modified version of the stop-signal task, Brevers et al (2018) estimated proactive inhibitory control by increased go-signal RT as a function of increased stop-signal probability ( i.e ., a higher change in go-signal RTs per stop-signal probability unit indicated a better capacity for proactive inhibitory control) and reported that elite athletes exhibited superior proactive inhibitory control.…”
Section: Discussionmentioning
confidence: 99%